The Relationship between Trade Integration and Economic Growth : Case of ASEAN-5 Countries - Balasubramaniam, Arunnan; Shazali, Abu Mansor; Puah, Chin Hong (Walter de Gruyter GmbH, 2016)
This paper studies how regional trade among ASEAN-5 countries (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) help in expanding the member countries' output. This paper applies ARDL bound testing approach with instrumental variables to explore the relationship and finds that estimates is in range of 0.27-0.55%. The paper concludes that trade integration should be promoted in order to stimulate economic growth within each country